A Time Variant Outdoor-to-Indoor Channel Model for Mobile Radio Based Navigation Applications - Wei Wang; Thomas Jost; Uwe-Carsten Fiebig; Wolfgang Koch (International Journal of Antennas and Propagation)
Time based positioning with terrestrial mobile radio signals has gained remarkable attention. To develop and validate positioning algorithms under realistic conditions, an accurate knowledge of the propagation channel is significant. However, there is still a lack of outdoor-to-indoor channel models suitable for positioning applications. To be applicable for positioning, the channel model has to fulfill three requirements that have not been accurately considered so far: the non-line-of-sight bias (affecting ranging accuracy), nondiscrete valued channel parameters (affecting algorithm performance), and the evolution of individual multipath components (MPCs) with time (affecting tracking performance). In this paper, an outdoor-to-indoor channel model is proposed based on an extension of the geometry-based stochastic modeling approach to fulfill the requirements. We consider MPCs occurring due to reflection, scattering, and combinations of both. In the model, three different types of MPCs are modeled separately according to their characteristics. Each MPC is represented by a fixed scatterer, which has a fixed position while the receiver antenna is moving. The parameters of the outdoor-to-indoor channel model are extracted from two channel measurement campaigns. The proposed outdoor-to-indoor channel model is capable of accurately simulating the time variant channel. A comparison of the channel model with the channel measurement data is performed by comparing statistics.